2022
DOI: 10.1088/1361-6463/ac4e35
|View full text |Cite
|
Sign up to set email alerts
|

Multi-inception patterns of emitter array/collector systems in DC corona discharge

Abstract: Multiple emitters systems have been previously used so as to increase charge density in the drift region, many times without producing sensible increment neither in total current nor ionic wind. This contribution focuses on analyzing the detailed physics behind this failure, that is named "multiple emitters un-scalability". It is established that multiple emitters un-scalability is related to the inability of multiple corona discharge inceptions when increasing the emitter number and/or density. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Other studies have also noted the presence of reverse emission, attributing it to a corona discharge at the collector [18,20] or to streamer discharges [21]. In Xu et al [18], our group showed that reverse emission causes deviations from the predictions of EAD theory: in particular, more power is required to produce a given thrust than predicted by theory.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Other studies have also noted the presence of reverse emission, attributing it to a corona discharge at the collector [18,20] or to streamer discharges [21]. In Xu et al [18], our group showed that reverse emission causes deviations from the predictions of EAD theory: in particular, more power is required to produce a given thrust than predicted by theory.…”
Section: Introductionmentioning
confidence: 67%
“…As suggested by Lemetayer et al [21], deviations in either I Vabe or FN Vabe from the linear relationship with voltage can be interpreted as evidence of reverse emission.…”
Section: Mitigating Reverse Emission: Collector Diameter Span and End...mentioning
confidence: 81%
See 1 more Smart Citation
“…First and foremost, the phenomenon of multiple emitters unscalability represents the main scientific limit for such thrusters. In fact, in several systems [13][14][15][16][17] it has been observed that increasing the number of the emitters does not lead to a proportional increase in the ionic wind, because an array of emitters at the same potential may create a local region of low potential gradient with detrimental effect on the emitter-collector field, and this effect can be worsened by the hydrodynamic interactions between parallel ionic wind jets. This shielding effect, mathematically described as a deviation from Peek's inception law [18], increases the inception voltage of the emitters.…”
Section: Parameter Spacementioning
confidence: 99%
“…In recent years, several studies have been done on the use of corona discharge as a propulsion system [31][32][33][34][35][36][37][38]. In 2011, Martins and Pinheiro investigated the nature of the driving force in a positive corona discharge using an asymmetric capacitor geometry.…”
Section: Introductionmentioning
confidence: 99%